Karakteristik Mikroemulsi Minyak Daun Sirih (Piper betle L.) pada Perlakuan Rasio Campuran Surfaktan dan Minyak Daun Sirih - Prasanta, I Putu Hendra Adi; Suhendra, Lutfi; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 4 (2021): DesemberDO - 10.24843/JRMA.2021.v09.i04.p14, 2022)
This study aims to determine the effect of the mixture ratio of surfactant and betel leaf oil on the characteristics of the microemulsion of betel leaf oil and determine the ratio of the mixture of surfactant and betel leaf oil that is appropriate to obtain the best microemulsion characteristics. This experiment used a Randomized Block Design (RAK), using the surfactant: betel leaf oil ratio treatment with 10 levels, namely 100:0; 98:2; 96:4; 94:6; 92:8; 90:10; 88:12; 86:14; 84:16 and 82:18. Grouping based on processing time. The best microemulsion is the microemulsion which has the highest concentration of betel leaf oil. The best microemulsion was tested for stability against pH and dilution during 8 weeks of storage. The turbidity index value is tested every 2 weeks. The rate of damage was calculated using linear regression analysis. The microemulsion was made by mixing the surfactant and betel leaf oil (5 ml in the oil phase), then adding the demineralized distilled water (water phase) dropwise in volume (10 ml). The microemulsion was incubated for 24 hours and calibrated using a spectrophotometer at a wavelength of 502 nm. The results showed that the ratio of the mixture of surfactants and betel leaf oil had an effect on the characteristics of the microemulsion of betel leaf oil. The ratio of surfactant and betel oil 94:6 is the best treatment for making betel leaf oil microemulsion with microemulsion characteristics that have a transparent appearance, turbidity index values ??before and after centrifugation are 0.225±0.005% and 0.196±0.005% and have a particle size of 14.8 ±6.9 nm, and the largest droplet size was 11 nm. Betel leaf oil microemulsion with surfactant and betel leaf oil ratio of 94:6 was stable for 8 weeks of storage. Keywords: microemulsion, ratio, surfactant, Piper betle Linn.